A critical review on advanced anaerobic membrane bioreactors (AnMBRs) for wastewater treatment: advanced membrane materials and energy demand. Issue 10 (25th August 2022) - Mahmood, Zarak; Cheng, Hui; Tian, Miao
Abstract : Insights into membrane design, reactor configurations, energy balance analysis and concerning challenges in AnMBR application for wastewater treatment. Abstract : Wastewater treatment not only protects our environment and human health but also conserves resources and recovers energy. Requiring less energy, achieving higher effluent quality, more efficient organic carbon capture (in the form of methane), and complete sludge retention than other conventional wastewater treatment methods, anaerobic membrane bioreactor (AnMBR) technology has attracted significant attention in the research and industrial fields. Significant progress has been made in AnMBR configuration, membrane materials and operational optimization in the past few decades. Here, we reviewed the progress on key elements of AnMBRs including anaerobic digestion, advanced membrane materials, and the latest designs of AnMBR. Membrane fouling, a critical issue in AnMBRs, was correlated with the membrane materials and systematic designs. Additionally, we also summarized the emerging AnMBR configurations and their efficiencies to overcome the limits of this technology. Most importantly, the energy demand and resource recovery from wastewater by AnMBRs are highlighted to cope with the recent worldwide energy crisis.